Dampak Artificial Intelligence terhadap Perubahan Perilaku Komunikasi bagi Manusia - Harahap, Hilda Rahmadani; Siregar, Tetti Saidah; Sinaga, Shilfy Zehana Aqilah; Siregar, Nadya Feriska; Sahara, Elvi; Mahyuti, Muhammad Aziz (VISA: Journal of Vision and Ideas, 2024)
The aim of this research is to analyze the influence of artificial intelligence (AI) on changes in people's communication behavior. The research method used is qualitative with a descriptive approach which includes library research, observation and document review. The research results show that artificial intelligence has a significant and complex impact on human communication behavior. The positive impacts of artificial intelligence include increasing communication efficiency with the help of chatbots and virtual assistants that speed up responses and increase user satisfaction. Additionally, artificial intelligence allows for more effective personalization of messages, which is especially useful in digital marketing. But the research also uncovers ethical and data protection issues surrounding the use of artificial intelligence, including the risks of personal data thickness and algorithmic bias, which can amplify social disempowerment. Another negative impact is the decline in people's ability to communicate and excessive dependence on technology, which can lead to bad behavior such as cyberbullying and the spread of fake news. Therefore, it is important to understand the long-term impact of AI on human interactions and determine strategies to maximize the benefits and minimize the associated risks.